Preparation technology of PVC carbon dioxide high foaming thermal insulation material
Through the preparation of modified plasticizers and composite stabilizers, combined with the high foaming process of carbon dioxide, the problems of poor toughness, flame retardancy and thermal stability of PVC foam insulation materials are solved, and the performance of the material is significantly improved and suitable for high-quality products. Performance application.
Patent Information
- Application Number
- CN202411111006.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-14
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-08-14
AI Technical Summary
The poor toughness, flame retardancy and thermal stability of existing PVC foam insulation materials limit their widespread use in high-performance applications.
Using the preparation method of modified plasticizer and composite stabilizer, the preparation method is carried out by 9,10-dihydro-9-oxa-10-phosphophenophen-10-oxide, diethyl hydroxymethylphosphonate, octamethyl Modified plasticizers are prepared by raw materials such as cyclotetrasiloxane and KH-570, and composite stability is prepared by raw materials using diethylene glycol butyl ether, zinc oxide, 6-amino-1,3-dimethyluracil and n-hexanal as raw materials. Combined with the high foaming process of carbon dioxide, it improves the toughness, flame retardancy and thermal stability of PVC materials.
It significantly improves the toughness, flame retardancy and thermal stability of PVC carbon dioxide high foam insulation materials, and enhances its applicability in high-performance applications.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of foaming thermal insulation material preparation, and in particular relates to a preparation process of PVC carbon dioxide high-foaming thermal insulation material. Background Art
[0002] With the progress and development of science and technology in my country, the performance of foam insulation materials has been gradually developed and recognized, and its application areas have been continuously expanded. At present, foam insulation materials have been spread throughout various industries. In addition to traditional industries such as construction, industry, and daily necessities, foam insulation materials have gradually occupied an important position in high-tech fields such as national defense and aerospace.
[0003] Compared with unfoamed PVC, the impact strength, toughness, fatigue life and thermal stability of PVC foam insulation materials have been improved. It has the characteristics of light weight, corrosion resistance, moisture resistance, low thermal conductivity, good thermal insulation performance, excellent weather resistance, etc. It is comparable to wood and can be processed like natural wood. With the continuous reduction of global wood resources, the use of PVC foam insulation materials to replace wood will become an important trend in the development of PVC materials in the future. However, due to the performance defects of PVC resin itself, the preparation of high-performance PVC insulation materials requires the optimization of its formula and foaming process so that it can be more widely used in life.
[0004] Patent CN111592682A discloses a preparation process of microporous foamed particles with flame retardant properties. The process introduces carbon dioxide into the interior of pre-foamed particles, and then undergoes a foaming process so that the carbon dioxide can form bubble pores and be stored inside the particles. During combustion, the carbon dioxide acts as a non-combustible gas, diluting the concentration of combustible gas decomposed from the combustibles to below the lower combustion limit. It also has a diluting effect on the oxygen concentration in the combustion zone, preventing the continuation of combustion, achieving a flame retardant effect, being more environmentally friendly and having a lower cost. However, the toughness, flame retardancy and thermal stability of the microporous foamed particles prepared by this method still have room for improvement. Summary of the invention
[0005] The purpose of the present invention is to provide a preparation process of a PVC carbon dioxide high-foam thermal insulation material, which is used to solve the technical problems of poor toughness, flame retardancy and thermal stability of the thermal insulation material in the prior art.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The present invention provides a preparation process of a PVC carbon dioxide high foaming thermal insulation material, comprising the following steps:
[0008] Step (1): fully mixing the dried PVC, modified plasticizer, composite stabilizer and calcium stearate and adding them to a drying oven for pre-plasticization, then adding them to a micro-mixing rheometer for extrusion, drying, and injection molding to obtain a PVC sheet;
[0009] Step (2): adding the PVC sheet into the autoclave and sealing it, placing the autoclave into an oil bath for temperature control, purging the autoclave with carbon dioxide, replacing the air in the autoclave and then introducing carbon dioxide, and when the dissolution equilibrium is reached, slowly releasing the pressure and taking out the treated PVC sheet;
[0010] Step (3): adding the treated PVC sheet into an oil bath, soaking, and cooling to obtain a PVC carbon dioxide high foaming thermal insulation material.
[0011] Preferably, the method for preparing the modified plasticizer comprises the following steps:
[0012] Q1: 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and ethanol are added to a reaction container, heated, and formaldehyde aqueous solution is added dropwise during stirring, and the dropping time is controlled. After the dropping is completed, the temperature is raised to reflux, and the mixture is allowed to stand for cooling, filtered, dried, recrystallized, and washed to obtain intermediate product 1. Intermediate product 1, dichloromethane, and triethanolamine are added to a reaction container, stirred to dissolve, and then a dichloromethane solution containing acryloyl chloride is added dropwise, and the dropping time is controlled. The mixture is reacted at low temperature. After the reaction is completed, extraction, rotary evaporation, and chromatography are performed to obtain intermediate product 2;
[0013] Q2: Add diethyl hydroxymethylphosphonate, dichloromethane and triethanolamine into a container, stir at low temperature, then drop a dichloromethane solution containing acryloyl chloride, control the dropping time, react at low temperature, then heat the reaction, after the reaction is completed, wash with water, rotary evaporate, and chromatograph to obtain intermediate product 3;
[0014] Q3: Octamethylcyclotetrasiloxane, KH-570, dodecylbenzenesulfonic acid and deionized water are mixed and stirred, pre-emulsified to obtain a pre-emulsion, 20% of the pre-emulsion, dodecylbenzenesulfonic acid and deionized water are added to a container, heated in a constant temperature water bath, and then the remaining pre-emulsion is added dropwise, reacted after the addition is completed, and cooled to obtain an intermediate product 4;
[0015] Q4: The pH of the intermediate product 4 is adjusted with a sodium hydroxide solution. After the adjustment, potassium persulfate is added to obtain a composite emulsion. The intermediate product 2, the intermediate product 3, sodium dodecyl sulfate and deionized water are mixed and stirred, and then added dropwise to the composite emulsion. After the dropwise addition is completed, the reaction is carried out, the temperature is lowered, the emulsion is broken, the filter is filtered, the washing is carried out, and the drying is carried out to obtain a modified plasticizer.
[0016] In the above process, the modified plasticizer is composed of a core layer and a shell layer, the core layer is mainly composed of octamethylcyclotetrasiloxane, and the shell layer is obtained by the reaction of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, diethyl hydroxymethylphosphonate and acryloyl chloride, and KH-570 is used as a crosslinking agent. The synthesis reaction formula of the shell layer is as follows:
[0017]
[0018] Preferably, in Q1, the dosage ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, ethanol and formaldehyde aqueous solution is (43.23-64.85) g: (100-150) mL: (20.13-30.2) mL, the heating temperature is 60-65°C, the volume fraction of formaldehyde aqueous solution is 37vt%, the dropping time is 30-45 min, the heating reflux temperature is 70-80°C, the time is 5-7h, the molar ratio of the intermediate product 1, triethanolamine and acryloyl chloride is (0.02-0.04): (0.03-0.06): (0.024-0.048), the temperature when the dichloromethane solution containing acryloyl chloride is added dropwise is -8~-10°C, the dropping time is 30-45 min, the low-temperature reaction temperature is -5~-8°C, and the reaction time is 10-12h.
[0019] Preferably, in Q2, the molar ratio of diethyl hydroxymethylphosphonate, triethanolamine and acryloyl chloride is (0.1-0.2): (0.1-0.2): (0.1-0.2), the low temperature stirring temperature is -5~-8°C, the stirring time is 30-45min, the dropwise addition time is controlled to be 10-20min, the low temperature reaction temperature is -5~-7°C, the time is 1-2h, the heating reaction temperature is 30-40°C, and the time is 10-12h; in Q3, octamethylcyclotetrasiloxane, KH-550, The dosage ratio of dodecylbenzenesulfonic acid and deionized water is (23-35) g: (2-3) g: (0.38-0.57) g: (37.5-56.3) mL, the stirring speed is 600-800 rpm, the pre-emulsification time is 30-45 min, the dosage ratio of 20% pre-emulsion, dodecylbenzenesulfonic acid and deionized water is (8-12) mL: (0.25-0.37) g: (25-35) mL, the constant temperature water bath heating time is 80-90 ° C, and the reaction time is 3-4.5 h.
[0020] Preferably, in Q4, the weight fraction of sodium hydroxide is 3wt%, the pH is adjusted to 8-8.5, the dosage ratio of intermediate product 2, intermediate product 3, sodium dodecyl sulfate, deionized water and composite emulsion is (18-27) g: (36-54) g: (0.5-0.75) g: (85-120) mL: (30-35) mL, the dropping speed is 1 drop / s, the reaction temperature is 80-85°C, and the reaction time is 3-4h.
[0021] Preferably, the preparation method of the composite stabilizer comprises the following steps:
[0022] S1: adding diethylene glycol butyl ether and zinc oxide to oleic acid, heating for reaction, and distilling under reduced pressure to obtain an intermediate product A;
[0023] S2: Add 6-amino-1,3-dimethyluracil and deionized water to a reaction container, stir to dissolve, add n-hexanal, stir to react, and after the reaction is completed, filter, wash, and dry to obtain an intermediate product B;
[0024] S3: The intermediate product A and the intermediate product B are mixed and stirred to obtain a composite stabilizer.
[0025] In the above process, the synthesis reaction formula of intermediate product B is as follows:
[0026]
[0027] The results of mass spectrometry analysis were: m / z: 392.22 (100.0%), 393.22 (19.9%), 394.22 (3.1%), 393.21 (2.2%).
[0028] Preferably, in S1, the mass ratio of diethylene glycol butyl ether, zinc oxide and oleic acid is (2-3) g: (8.14-12.21) g: (2.14-3.12) g, the heating reaction temperature is 80-90°C, and the reaction time is 2-3 h; in S2, the molar ratio of 6-amino-1,3-dimethyluracil and n-hexanal is (2-3): (1-1.5), and the stirring reaction time is 20-24 h; in S3, the amount ratio of intermediate product A and intermediate product B is (10-12) mL: (4-6) g, and the mixing and stirring time is 4-6 h.
[0029] Preferably, in step (1), the drying temperature is 50-60°C, the drying time is 20-24h, the mass ratio of PVC, modified plasticizer, composite stabilizer and calcium stearate is (100-120)g: (8-12)g: (6-7)g: (1-2)g, the pre-plasticizing temperature is 70-80°C, and the pre-plasticizing process is stirred once every 10 minutes for 5-7 times. During the extrusion process, the temperature of the micro-mixing rheometer is set to 180-190°C, the screw speed is 30-40rpm, and during the injection molding process, the injection molding temperature is 200-220°C, the mold temperature is 90-95°C, and the injection molding pressure is 800-1000bar.
[0030] Preferably, in step (2), the temperature is controlled at 40-50°C, the time is controlled at 30-45min, the introduction time is 50-55h, and the saturated pressure at the dissolution equilibrium is 13-15MPa.
[0031] Preferably, in step (3), the soaking temperature is 180-220°C.
[0032] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0033] 1. The present invention first uses 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, acryloyl chloride, diethyl hydroxymethylphosphonate, octamethylcyclotetrasiloxane and KH-570 as raw materials to prepare a modified plasticizer, and then uses diethylene glycol butyl ether, zinc oxide, 6-amino-1,3-dimethyluracil and n-hexanal as raw materials to prepare a composite stabilizer, which is used in PVC carbon dioxide high foaming thermal insulation material, so that the obtained thermal insulation material has excellent toughness, flame retardancy and thermal stability.
[0034] 2. The present invention uses octamethylcyclotetrasiloxane as a core layer, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, acryloyl chloride and diethyl hydroxymethylphosphonate as raw materials to prepare a shell layer, and then uses KH-550 as a crosslinking agent to prepare a modified plasticizer, which is added to PVC for foaming raw materials, so that the obtained thermal insulation material has excellent toughness and flame retardancy. The carbon chain and polar group in the modified plasticizer can form an intermolecular force with the chlorine atoms on the PVC chain, reducing the interaction force between the PVC chains, making the PVC chains easier to slide, and improving its flexibility and elongation. The modified plasticizer molecules can be inserted into the gaps in the PVC chain to achieve lubrication and filling effects, reduce friction between chain segments, and cause them to deform instead of break when subjected to external force, thereby improving their toughness; at the same time, the flame retardant contained in the modified plasticizer can produce non-combustible gas when burned, dilute the oxygen concentration in the air, and take away some heat, thereby reducing the combustion speed and flame temperature. The flame retardant contained in the modified plasticizer can form a dense protective layer on the surface of the PVC material, isolating oxygen and heat from transferring to the inside, inhibiting the combustion, and thus achieving the purpose of flame retardancy.
[0035] 3. The present invention uses diethylene glycol butyl ether, zinc oxide, 6-amino-1,3-dimethyluracil and n-hexanal as raw materials to prepare a composite stabilizer. When the composite stabilizer is added to the process of carbon dioxide foaming PVC material, the obtained thermal insulation material can have excellent thermal stability. The composite stabilizer can react with HCl generated during the degradation of PVC to slow down the degradation reaction of PVC. At the same time, the generated ammonium salt can also inhibit the further degradation of PVC and enhance the thermal stability of the foamed thermal insulation material. DETAILED DESCRIPTION
[0036] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Example 1
[0038] This embodiment discloses a method for preparing a modified plasticizer, comprising the following steps:
[0039] Q1: 54.04 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 125 mL of ethanol were added to a reaction vessel, heated to 65°C, and 25.17 mL of a 37% formaldehyde aqueous solution was added dropwise during stirring, and the addition time was controlled to be 30 min. After the addition was completed, the temperature was raised to 80°C and refluxed for 6 h, and the mixture was allowed to stand for cooling, filtered, dried, recrystallized, and washed to obtain intermediate product 1. 7.41 g of intermediate product 1, 20 mL of dichloromethane, and 6.51 mL of triethanolamine were added to a reaction vessel, stirred to dissolve, and then 10 mL of a dichloromethane solution containing 2.93 mL of acryloyl chloride was added dropwise at -10°C, and the addition time was controlled to be 30 min. The mixture was reacted at -8°C for 12 h. After the reaction was completed, the mixture was extracted, rotary evaporated, and chromatographed to obtain intermediate product 2.
[0040] Q2: Add 25.2g of diethyl hydroxymethylphosphonate, 50mL of dichloromethane and 15.15g of triethanolamine to a container, stir at -5°C for 45min, then drop 20mL of dichloromethane solution containing 13.5g of acryloyl chloride, control the dropping time to 15min, react at -7°C for 2h, then heat to 35°C for 12h, after the reaction, wash with water, rotary evaporate, and chromatograph to obtain intermediate 3;
[0041] Q3: 29 g of octamethylcyclotetrasiloxane, 2.5 g of KH-570, 0.48 g of dodecylbenzenesulfonic acid and 46.9 mL of deionized water were mixed and stirred, and pre-emulsified at 800 rpm for 45 min to obtain a pre-emulsion. 10 mL of the pre-emulsion, 0.31 g of dodecylbenzenesulfonic acid and 30 mL of deionized water were added to a container, heated in a constant temperature water bath at 80°C, and then 40 mL of the pre-emulsion was added dropwise. After the addition was completed, the reaction was allowed to proceed for 3 h, and the temperature was lowered to obtain an intermediate product 4.
[0042] Q4: Use a sodium hydroxide solution with a weight fraction of 3wt% to adjust the pH of the intermediate product 4 to 8. After the adjustment, add 0.5g of potassium persulfate to obtain a composite emulsion. Mix 22.5g of intermediate product 2, 45g of intermediate product 3, 0.63g of sodium dodecyl sulfate and 103mL of deionized water, stir and add them to 32.5mL of the composite emulsion at a rate of 1 drop / s. After the addition is complete, react at 80℃ for 4h, cool, demulsify, filter, wash and dry to obtain a modified plasticizer.
[0043] This embodiment discloses a method for preparing a composite stabilizer, comprising the following steps:
[0044] S1: Add 2.5 g of diethylene glycol butyl ether and 10.18 g of zinc oxide to 2.63 g of oleic acid, heat at 90°C for 3 h, and distill under reduced pressure to obtain intermediate product A;
[0045] S2: Add 3.88 g of 6-amino-1,3-dimethyluracil and 250 mL of deionized water to a reaction container, stir to dissolve, add 1.25 g of n-hexanal, stir to react for 24 h, and after the reaction is completed, filter, wash, and dry to obtain intermediate product B;
[0046] S3: 11 mL of intermediate product A and 5 g of intermediate product B were mixed and stirred for 6 h to obtain a composite stabilizer.
[0047] This embodiment discloses a preparation process of a PVC carbon dioxide high foaming thermal insulation material, comprising the following steps:
[0048] Step (1): 110 g of PVC dried at 60° C. for 24 hours, 10 g of a modified plasticizer, 6.5 g of a composite stabilizer and 1.5 g of calcium stearate are fully mixed and added to an 80° C. drying oven for pre-plasticization. During the pre-plasticization process, the mixture is stirred every 10 minutes for 6 times. The mixture is then added to a micro-mixing rheometer for extrusion. During the extrusion process, the temperature of the micro-mixing rheometer is set to 185° C., the screw speed is set to 35 rpm, and the mixture is dried. The mixture is then injection molded in a micro-injection molding machine at an injection temperature of 220° C., a mold temperature of 90° C. and an injection pressure of 800 bar to obtain a PVC sheet.
[0049] Step (2): Add the PVC sheet into the autoclave and seal it, place the autoclave in an oil bath and control the temperature to 40°C for 35 minutes, purge the autoclave with carbon dioxide, replace the air in the autoclave and then introduce carbon dioxide for 55 hours, and when the saturated pressure reaches 13 MPa, slowly release the pressure and take out the treated PVC sheet;
[0050] Step (3): adding the treated PVC sheet into a 200° C. oil bath, soaking, and cooling to obtain a PVC carbon dioxide high foaming thermal insulation material.
[0051] Example 2
[0052] This embodiment discloses a method for preparing a modified plasticizer, comprising the following steps:
[0053] Q1: 43.23 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 100 mL of ethanol were added to a reaction vessel, heated to 65°C, and 20.13 mL of a 37% formaldehyde aqueous solution was added dropwise during stirring, and the addition time was controlled to be 30 min. After the addition was completed, the temperature was raised to 80°C and refluxed for 6 h, and the mixture was allowed to stand for cooling, filtered, dried, recrystallized, and washed to obtain intermediate product 1. 4.94 g of intermediate product 1, 20 mL of dichloromethane, and 4.34 mL of triethanolamine were added to a reaction vessel, stirred to dissolve, and then 10 mL of a dichloromethane solution containing 1.95 mL of acryloyl chloride was added dropwise at -10°C, and the addition time was controlled to be 30 min. The mixture was reacted at -8°C for 12 h. After the reaction was completed, the mixture was extracted, rotary evaporated, and chromatographed to obtain intermediate product 2.
[0054] Q2: 16.8 g of diethyl hydroxymethylphosphonate, 50 mL of dichloromethane and 10.1 g of triethanolamine were added to a container, stirred at -5°C for 45 min, and then 20 mL of a dichloromethane solution containing 9 g of acryloyl chloride was added dropwise, the addition time was controlled to be 15 min, the reaction was carried out at -7°C for 2 h, and then the temperature was raised to 35°C for 12 h. After the reaction was completed, the product was washed with water, rotary evaporated, and chromatographed to obtain intermediate product 3;
[0055] Q3: 23 g of octamethylcyclotetrasiloxane, 2 g of KH-570, 0.38 g of dodecylbenzenesulfonic acid and 56.3 mL of deionized water were mixed and stirred, and pre-emulsified at 800 rpm for 45 min to obtain a pre-emulsion. 8 mL of the pre-emulsion, 0.25 g of dodecylbenzenesulfonic acid and 25 mL of deionized water were added to a container, heated in a constant temperature water bath at 80°C, and then 32 mL of the pre-emulsion was added dropwise. After the addition was completed, the reaction was allowed to proceed for 3 h, and the temperature was lowered to obtain an intermediate product 4.
[0056] Q4: Use a sodium hydroxide solution with a weight fraction of 3wt% to adjust the pH of the intermediate product 4 to 8. After the adjustment, add 0.5g of potassium persulfate to obtain a composite emulsion. Mix 18g of the intermediate product 2, 36g of the intermediate product 3, 0.5g of sodium dodecyl sulfate and 85mL of deionized water, stir and add them into 30mL of the composite emulsion at a rate of 1 drop / s. After the addition is complete, react at 80°C for 4h, cool, demulsify, filter, wash and dry to obtain a modified plasticizer.
[0057] This embodiment discloses a method for preparing a composite stabilizer, comprising the following steps:
[0058] S1: Add 2 g of diethylene glycol butyl ether and 8.14 g of zinc oxide to 2.14 g of oleic acid, heat at 90°C for 3 h, and distill under reduced pressure to obtain intermediate product A;
[0059] S2: Add 3.1 g of 6-amino-1,3-dimethyluracil and 250 mL of deionized water to a reaction container, stir to dissolve, add 1 g of n-hexanal, stir to react for 24 h, and after the reaction is completed, filter, wash, and dry to obtain intermediate product B;
[0060] S3: 10 mL of intermediate product A and 4 g of intermediate product B were mixed and stirred for 6 h to obtain a composite stabilizer.
[0061] This embodiment discloses a preparation process of a PVC carbon dioxide high foaming thermal insulation material, comprising the following steps:
[0062] Step (1): 100 g of PVC dried at 60° C. for 24 hours, 8 g of a modified plasticizer, 6 g of a composite stabilizer and 1 g of calcium stearate are fully mixed and added to an 80° C. drying oven for pre-plasticization. During the pre-plasticization process, the mixture is stirred every 10 minutes for 6 times. The mixture is then added to a micro-mixing rheometer for extrusion. During the extrusion process, the temperature of the micro-mixing rheometer is set to 185° C., the screw speed is set to 35 rpm, and the mixture is dried. The mixture is then injection molded in a micro-injection molding apparatus at an injection molding temperature of 220° C., a mold temperature of 90° C. and an injection molding pressure of 800 bar to obtain a PVC sheet.
[0063] Step (2): Add the PVC sheet into the autoclave and seal it, place the autoclave in an oil bath and control the temperature to 40°C for 35 minutes, purge the autoclave with carbon dioxide, replace the air in the autoclave and then introduce carbon dioxide for 55 hours, and when the saturated pressure reaches 13 MPa, slowly release the pressure and take out the treated PVC sheet;
[0064] Step (3): adding the treated PVC sheet into a 200° C. oil bath, soaking, and cooling to obtain a PVC carbon dioxide high foaming thermal insulation material.
[0065] Example 3
[0066] This embodiment discloses a method for preparing a modified plasticizer, comprising the following steps:
[0067] Q1: 64.85 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 150 mL of ethanol were added to a reaction vessel, heated to 65°C, and 30.2 mL of a 37% formaldehyde aqueous solution was added dropwise during stirring, and the addition time was controlled to be 30 min. After the addition was completed, the temperature was raised to 80°C and refluxed for 6 h, and the mixture was allowed to stand and cool, filtered, dried, recrystallized, and washed to obtain intermediate product 1. 9.88 g of intermediate product 1, 20 mL of dichloromethane, and 8.68 mL of triethanolamine were added to a reaction vessel, stirred to dissolve, and then 10 mL of a dichloromethane solution containing 3.9 mL of acryloyl chloride was added dropwise at -10°C, and the addition time was controlled to be 30 min. The mixture was reacted at -8°C for 12 h. After the reaction was completed, the mixture was extracted, rotary evaporated, and chromatographed to obtain intermediate product 2.
[0068] Q2: 33.6 g of diethyl hydroxymethylphosphonate, 50 mL of dichloromethane and 20.2 g of triethanolamine were added to a container, stirred at -5°C for 45 min, and then 20 mL of a dichloromethane solution containing 18 g of acryloyl chloride was added dropwise, the addition time was controlled to be 15 min, the reaction was carried out at -7°C for 2 h, and then the temperature was raised to 35°C for 12 h. After the reaction was completed, the product was washed with water, rotary evaporated, and chromatographed to obtain intermediate product 3;
[0069] Q3: 35 g of octamethylcyclotetrasiloxane, 3 g of KH-570, 0.57 g of dodecylbenzenesulfonic acid and 37.5 mL of deionized water were mixed and stirred, and pre-emulsified at 800 rpm for 45 min to obtain a pre-emulsion. 12 mL of the pre-emulsion, 0.37 g of dodecylbenzenesulfonic acid and 35 mL of deionized water were added to a container, heated in a constant temperature water bath at 80°C, and then 48 mL of the pre-emulsion was added dropwise. After the addition was completed, the reaction was allowed to proceed for 3 h, and the temperature was lowered to obtain an intermediate product 4.
[0070] Q4: Use a sodium hydroxide solution with a weight fraction of 3wt% to adjust the pH of the intermediate product 4 to 8. After the adjustment, add 0.5g of potassium persulfate to obtain a composite emulsion. Mix 27g of the intermediate product 2, 54g of the intermediate product 3, 0.75g of sodium dodecyl sulfate and 120mL of deionized water, stir and add them into 35mL of the composite emulsion at a rate of 1 drop / s. After the addition is complete, react at 80°C for 4h, cool, demulsify, filter, wash and dry to obtain a modified plasticizer.
[0071] This embodiment discloses a method for preparing a composite stabilizer, comprising the following steps:
[0072] S1: Add 3 g of diethylene glycol butyl ether and 12.21 g of zinc oxide to 3.12 g of oleic acid, heat at 90°C for 3 h, and distill under reduced pressure to obtain intermediate product A;
[0073] S2: Add 4.65 g of 6-amino-1,3-dimethyluracil and 250 mL of deionized water to a reaction container, stir to dissolve, add 1.5 g of n-hexanal, stir to react for 24 h, and after the reaction is completed, filter, wash, and dry to obtain intermediate product B;
[0074] S3: 12 mL of intermediate product A and 6 g of intermediate product B were mixed and stirred for 6 h to obtain a composite stabilizer.
[0075] This embodiment discloses a preparation process of a PVC carbon dioxide high foaming thermal insulation material, comprising the following steps:
[0076] Step (1): 120 g of PVC dried at 60° C. for 24 h, 12 g of a modified plasticizer, 7 g of a composite stabilizer and 2 g of calcium stearate are fully mixed and added to an 80° C. drying oven for pre-plasticization. During the pre-plasticization process, the mixture is stirred every 10 min for 6 times. The mixture is then added to a micro-mixing rheometer for extrusion. During the extrusion process, the temperature of the micro-mixing rheometer is set to 185° C., the screw speed is set to 35 rpm, and the mixture is dried. The mixture is then injection molded in a micro-injection molding apparatus at an injection temperature of 220° C., a mold temperature of 90° C. and an injection pressure of 800 bar to obtain a PVC sheet.
[0077] Step (2): Add the PVC sheet into the autoclave and seal it, place the autoclave in an oil bath and control the temperature to 40°C for 35 minutes, purge the autoclave with carbon dioxide, replace the air in the autoclave and then introduce carbon dioxide for 55 hours, and when the saturated pressure reaches 13 MPa, slowly release the pressure and take out the treated PVC sheet;
[0078] Step (3): adding the treated PVC sheet into a 200° C. oil bath, soaking, and cooling to obtain a PVC carbon dioxide high foaming thermal insulation material.
[0079] Example 4
[0080] This embodiment discloses a method for preparing a modified plasticizer, comprising the following steps:
[0081] Q1: 48.71 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 110 mL of ethanol were added to a reaction vessel, heated to 65°C, and 23.29 mL of a 37% formaldehyde aqueous solution was added dropwise during stirring, and the addition time was controlled to be 30 min. After the addition was completed, the temperature was raised to 80°C and refluxed for 6 h, and the mixture was allowed to stand and cool, filtered, dried, recrystallized, and washed to obtain intermediate product 1. 5.72 g of intermediate product 1, 20 mL of dichloromethane, and 5.27 mL of triethanolamine were added to a reaction vessel, stirred to dissolve, and then 10 mL of a dichloromethane solution containing 2.27 mL of acryloyl chloride was added dropwise at -10°C, and the addition time was controlled to be 30 min. The mixture was reacted at -8°C for 12 h. After the reaction was completed, the mixture was extracted, rotary evaporated, and chromatographed to obtain intermediate product 2.
[0082] Q2: Add 20.1g of diethyl hydroxymethylphosphonate, 50mL of dichloromethane and 12.7g of triethanolamine to a container, stir at -5°C for 45min, then drop 20mL of dichloromethane solution containing 11g of acryloyl chloride, control the dropping time to 15min, react at -7°C for 2h, then heat to 35°C for 12h, after the reaction, wash with water, rotary evaporate, and chromatograph to obtain intermediate 3;
[0083] Q3: 26 g of octamethylcyclotetrasiloxane, 2.1 g of KH-570, 0.43 g of dodecylbenzenesulfonic acid and 52.1 mL of deionized water were mixed and stirred, and pre-emulsified at 800 rpm for 45 min to obtain a pre-emulsion. 9 mL of the pre-emulsion, 0.34 g of dodecylbenzenesulfonic acid and 27.5 mL of deionized water were added to a container, heated in a constant temperature water bath at 80°C, and then 36 mL of the pre-emulsion was added dropwise. After the addition was completed, the reaction was allowed to proceed for 3 h, and the temperature was lowered to obtain an intermediate product 4.
[0084] Q4: Use a sodium hydroxide solution with a weight fraction of 3wt% to adjust the pH of the intermediate product 4 to 8. After the adjustment, add 0.5g of potassium persulfate to obtain a composite emulsion. Mix 20g of the intermediate product 2, 38g of the intermediate product 3, 0.55g of sodium dodecyl sulfate and 98mL of deionized water, stir and add them into 31mL of the composite emulsion at a rate of 1 drop / s. After the addition is complete, react at 80°C for 4h, cool, demulsify, filter, wash and dry to obtain a modified plasticizer.
[0085] This embodiment discloses a method for preparing a composite stabilizer, comprising the following steps:
[0086] S1: Add 2.1 g of diethylene glycol butyl ether and 9.35 g of zinc oxide to 2.38 g of oleic acid, heat at 90°C for 3 h, and distill under reduced pressure to obtain intermediate product A;
[0087] S2: Add 3.53 g of 6-amino-1,3-dimethyluracil and 250 mL of deionized water to a reaction container, stir to dissolve, add 1.1 g of n-hexanal, stir to react for 24 h, and after the reaction is completed, filter, wash, and dry to obtain intermediate product B;
[0088] S3: 10.5 mL of intermediate product A and 4.5 g of intermediate product B were mixed and stirred for 6 h to obtain a composite stabilizer.
[0089] This embodiment discloses a preparation process of a PVC carbon dioxide high foaming thermal insulation material, comprising the following steps:
[0090] Step (1): 105 g of PVC dried at 60° C. for 24 h, 9 g of a modified plasticizer, 6.2 g of a composite stabilizer and 1.2 g of calcium stearate are fully mixed and added to an 80° C. drying oven for pre-plasticization. During the pre-plasticization process, the mixture is stirred every 10 min for 6 times. The mixture is then added to a micro-mixing rheometer for extrusion. During the extrusion process, the temperature of the micro-mixing rheometer is set to 185° C., the screw speed is set to 35 rpm, and the mixture is dried. The mixture is then injection molded in a micro-injection molding apparatus at an injection molding temperature of 220° C., a mold temperature of 90° C. and an injection molding pressure of 800 bar to obtain a PVC sheet.
[0091] Step (2): Add the PVC sheet into the autoclave and seal it, place the autoclave in an oil bath and control the temperature to 40°C for 35 minutes, purge the autoclave with carbon dioxide, replace the air in the autoclave and then introduce carbon dioxide for 55 hours, and when the saturated pressure reaches 13 MPa, slowly release the pressure and take out the treated PVC sheet;
[0092] Step (3): adding the treated PVC sheet into a 200° C. oil bath, soaking, and cooling to obtain a PVC carbon dioxide high foaming thermal insulation material.
[0093] Comparative Example 1
[0094] Comparative Example 1 Compared with Example 1, in the preparation process of the modified plasticizer in Comparative Example 1, no 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was added, and other conditions remained unchanged.
[0095] Comparative Example 2
[0096] Comparative Example 2 Compared with Example 1, in the preparation process of the modified plasticizer in Comparative Example 2, no diethyl hydroxymethylphosphonate was added, and other conditions remained unchanged.
[0097] Comparative Example 3
[0098] Comparative Example 3 Compared with Example 1, in the preparation process of the composite stabilizer in Comparative Example 3, zinc oxide was not added, and other conditions remained unchanged.
[0099] Comparative Example 4
[0100] Comparative Example 4 Compared with Example 1, in the preparation process of the composite stabilizer in Comparative Example 4, 6-amino-1,3-dimethyluracil was not added, and other conditions remained unchanged.
[0101] Comparative Example 5
[0102] Comparative Example 5 Compared with Example 1, in the preparation process of the PVC carbon dioxide high-foaming thermal insulation material in Comparative Example 5, no modified plasticizer is added, and other conditions remain unchanged.
[0103] Comparative Example 6
[0104] Comparative Example 6 Compared with Example 1, in the preparation process of the PVC carbon dioxide high-foaming thermal insulation material in Comparative Example 6, no composite stabilizer is added, and other conditions remain unchanged.
[0105] The samples prepared according to Examples 1-4 and Comparative Examples 1-6 were subjected to performance tests, the tensile strength of the samples was tested according to GB / T 1040.1-2018, the flame retardant properties of the samples were tested according to HG / T 3747.3-2014, and the thermal stability of the samples was tested according to HG / T3311-2009. The test results are shown in Table 1:
[0106] Table 1
[0107] project Tensile strength / MPa Limiting oxygen index / % <![CDATA[M 氯化氢 / (mg)]]> Example 1 45.8 36.3 180 Example 2 45.5 35.4 183 Example 3 45.6 35.1 184 Example 4 45.3 35.3 187 Comparative Example 1 39.3 26.6 189 Comparative Example 2 39.1 26.1 188 Comparative Example 3 44.9 35.1 214 Comparative Example 4 45.1 35.2 228 Comparative Example 5 38.5 25.3 190 Comparative Example 6 44.8 34.9 232
[0108] It can be seen from the test results in Table 1 that the PVC carbon dioxide high foaming thermal insulation materials prepared in Examples 1-4 of the present invention have excellent toughness, flame retardancy and thermal stability. The better the thermal stability of PVC, the lower the content of hydrogen chloride generated during the heating process. From the comparison between comparative example 1 and examples 1-4, it can be seen that the addition of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide can make the obtained thermal insulation material have excellent toughness and flame retardancy; from the comparison between comparative example 2 and examples 1-4, it can be seen that the addition of diethyl hydroxymethylphosphonate can make the obtained thermal insulation material have excellent toughness and flame retardancy; from the comparison between comparative example 3 and examples 1-4, it can be seen that the addition of zinc oxide can make the obtained thermal insulation material have excellent thermal stability; from the comparison between comparative example 4 and examples 1-4, it can be seen that the addition of 6-amino-1,3-dimethyluracil can make the obtained thermal insulation material have excellent thermal stability; from the comparison between comparative example 5 and examples 1-4, it can be seen that the addition of modified plasticizer can make the obtained thermal insulation material have excellent toughness and flame retardancy; from the comparison between comparative example 6 and examples 1-4, it can be seen that the addition of composite stabilizer can make the obtained thermal insulation material have excellent thermal stability.
[0109] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
[0110] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. The preparation process of PVC carbon dioxide high foaming thermal insulation material is characterized by: The following steps are involved: Step (1): fully mixing the dried PVC, modified plasticizer, composite stabilizer and calcium stearate and adding them to a drying oven for pre-plasticization, then adding them to a micro-mixing rheometer for extrusion, drying, and injection molding to obtain a PVC sheet; Step (2): adding the PVC sheet into the autoclave and sealing it, placing the autoclave into an oil bath for temperature control, purging the autoclave with carbon dioxide, replacing the air in the autoclave and then introducing carbon dioxide, and when the dissolution equilibrium is reached, slowly releasing the pressure and taking out the treated PVC sheet; Step (3): adding the treated PVC sheet into an oil bath, soaking, and cooling to obtain a PVC carbon dioxide high foaming thermal insulation material; The preparation method of the modified plasticizer comprises the following steps: Q1: 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and ethanol are added to a reaction container, heated, and formaldehyde aqueous solution is added dropwise during stirring, and the dropping time is controlled. After the dropping is completed, the temperature is raised to reflux, and the mixture is allowed to stand for cooling, filtered, dried, recrystallized, and washed to obtain intermediate product 1. Intermediate product 1, dichloromethane, and triethanolamine are added to a reaction container, stirred to dissolve, and then a dichloromethane solution containing acryloyl chloride is added dropwise, and the dropping time is controlled. The mixture is reacted at low temperature. After the reaction is completed, extraction, rotary evaporation, and chromatography are performed to obtain intermediate product 2; Q2: Add diethyl hydroxymethylphosphonate, dichloromethane and triethanolamine into a container, stir at low temperature, then drop a dichloromethane solution containing acryloyl chloride, control the dropping time, react at low temperature, then heat the reaction, after the reaction is completed, wash with water, rotary evaporate, and chromatograph to obtain intermediate product 3; Q3: Octamethylcyclotetrasiloxane, KH-570, dodecylbenzenesulfonic acid and deionized water are mixed and stirred, pre-emulsified to obtain a pre-emulsion, 20% of the pre-emulsion, dodecylbenzenesulfonic acid and deionized water are added to a container, heated in a constant temperature water bath, and then the remaining pre-emulsion is added dropwise, reacted after the addition is completed, and cooled to obtain an intermediate product 4; Q4: The pH of the intermediate product 4 is adjusted with a sodium hydroxide solution. After the adjustment is completed, potassium persulfate is added to obtain a composite emulsion. The intermediate product 2, the intermediate product 3, sodium dodecyl sulfate and deionized water are mixed and stirred, and then added dropwise to the composite emulsion. After the dropwise addition is completed, the mixture is reacted, cooled, demulsified, filtered, washed, and dried to obtain a modified plasticizer. The preparation method of the composite stabilizer comprises the following steps: S1: adding diethylene glycol butyl ether and zinc oxide to oleic acid, heating for reaction, and distilling under reduced pressure to obtain an intermediate product A; S2: Add 6-amino-1,3-dimethyluracil and deionized water to a reaction container, stir to dissolve, add n-hexanal, stir to react, and after the reaction is completed, filter, wash, and dry to obtain an intermediate product B; S3: The intermediate product A and the intermediate product B are mixed and stirred to obtain a composite stabilizer.
2. The preparation process of the PVC carbon dioxide high foaming thermal insulation material according to claim 1, characterized in that: In the Q1, the dosage ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, ethanol and formaldehyde aqueous solution is (43.23-64.85) g: (100-150) mL: (20.13-30.2) mL, the heating temperature is 60-65°C, the volume fraction of formaldehyde aqueous solution is 37vt%, the dropping time is 30-45 min, the heating reflux temperature is 70-80°C, the time is 5-7h, the molar ratio of the intermediate product 1, triethanolamine and acryloyl chloride is (0.02-0.04): (0.03-0.06): (0.024-0.048), the temperature when the dichloromethane solution containing acryloyl chloride is added dropwise is -8~-10°C, the dropping time is 30-45 min, the low-temperature reaction temperature is -5~-8°C, and the reaction time is 10-12h.
3. The preparation process of the PVC carbon dioxide high foaming thermal insulation material according to claim 1, characterized in that: In the Q2, the molar ratio of diethyl hydroxymethylphosphonate, triethanolamine and acryloyl chloride is (0.1-0.2): (0.1-0.2): (0.1-0.2), the low temperature stirring temperature is -5~-8°C, the stirring time is 30-45min, the dropwise addition time is controlled to be 10-20min, the low temperature reaction temperature is -5~-7°C, the time is 1-2h, the heating reaction temperature is 30-40°C, and the time is 10-12h; in the Q3, octamethylcyclotetrasiloxane, KH-550, dodecacyclopentasiloxane, triethanolamine ... The dosage ratio of alkylbenzene sulfonic acid and deionized water is (23-35) g: (2-3) g: (0.38-0.57) g: (37.5-56.3) mL, the stirring speed is 600-800 rpm, the pre-emulsification time is 30-45 min, the dosage ratio of 20% pre-emulsion, dodecylbenzene sulfonic acid and deionized water is (8-12) mL: (0.25-0.37) g: (25-35) mL, the constant temperature water bath heating time is 80-90 ° C, and the reaction time is 3-4.5 h.
4. The preparation process of the PVC carbon dioxide high foaming thermal insulation material according to claim 1, characterized in that: In the Q4, the weight fraction of sodium hydroxide is 3wt%, the pH is adjusted to 8-8.5, the dosage ratio of the intermediate product 2, the intermediate product 3, sodium dodecyl sulfate, deionized water and the composite emulsion is (18-27) g: (36-54) g: (0.5-0.75) g: (85-120) mL: (30-35) mL, the dropping speed is 1 drop / s, the reaction temperature is 80-85°C, and the reaction time is 3-4h.
5. The preparation process of the PVC carbon dioxide high foaming thermal insulation material according to claim 1, characterized in that: In S1, the mass ratio of diethylene glycol butyl ether, zinc oxide and oleic acid is (2-3) g: (8.14-12.21) g: (2.14-3.12) g, the heating reaction temperature is 80-90° C., and the reaction time is 2-3 h. In S2, the molar ratio of 6-amino-1,3-dimethyluracil and n-hexanal is (2-3): (1-1.5), and the stirring reaction time is 20-24 h. In S3, the amount ratio of intermediate product A and intermediate product B is (10-12) mL: (4-6) g, and the mixing and stirring time is 4-6 h.
6. The preparation process of the PVC carbon dioxide high foaming thermal insulation material according to claim 1, characterized in that: In the step (1), the drying temperature is 50-60°C, the drying time is 20-24h, the mass ratio of PVC, modified plasticizer, composite stabilizer and calcium stearate is (100-120)g: (8-12)g: (6-7)g: (1-2)g, the pre-plasticizing temperature is 70-80°C, and the pre-plasticizing process is stirred once every 10 minutes for 5-7 times. During the extrusion process, the temperature of the micro-mixing rheometer is set to 180-190°C, the screw speed is 30-40rpm, and during the injection molding process, the injection molding temperature is 200-220°C, the mold temperature is 90-95°C, and the injection molding pressure is 800-1000bar.
7. The preparation process of the PVC carbon dioxide high foaming thermal insulation material according to claim 1, characterized in that: In the step (2), the temperature is controlled at 40-50°C, the time is controlled at 30-45min, the introduction time is 50-55h, and the saturated pressure at the dissolution equilibrium is 13-15MPa.
8. The preparation process of the PVC carbon dioxide high foaming thermal insulation material according to claim 1, characterized in that: In the step (3), the soaking temperature is 180-220°C.
Citation Information
Patent Citations
Preparation process and application of microcellular foamed particles with flame retardance
CN111592682A
Organosilicon-phosphorus-containing acrylate core-shell toughening flame retardant and preparation method thereof
CN114292368A
Preparation method and application of PVC (polyvinyl chloride) flame-retardant plasticizer
CN118324801A